2022
DOI: 10.4049/jimmunol.2101123
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cellular Immune Responses to SARS-CoV-2 in Pregnant Women

Abstract: Pregnant women are at increased risk of adverse outcomes, including preeclampsia and preterm birth, that may result from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Pregnancy imprints specific maternal immune responses that can modulate host susceptibility to microbial infection; therefore, recent studies have focused on the humoral response against SARS-CoV-2 in pregnant women. However, the pregnancy-specific cellular immune responses triggered by SARS-CoV-2 infection are poorly un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 119 publications
5
20
0
Order By: Relevance
“…Thus, given such deficiencies in peripheral adaptive immunity, pregnant women infected with SARS-CoV-2 may rely more heavily on monocytes, which are also potent contributors to anti-viral host defense 108 . Consistently, monocytes undergo substantial expansion and differentiation in patients with severe COVID-19 [109][110][111] , and we have shown that monocytes from pregnant women appear to undergo accelerated transition and activation in response to SARS-CoV-2 exposure 30 , which is in line with a previous report 39 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, given such deficiencies in peripheral adaptive immunity, pregnant women infected with SARS-CoV-2 may rely more heavily on monocytes, which are also potent contributors to anti-viral host defense 108 . Consistently, monocytes undergo substantial expansion and differentiation in patients with severe COVID-19 [109][110][111] , and we have shown that monocytes from pregnant women appear to undergo accelerated transition and activation in response to SARS-CoV-2 exposure 30 , which is in line with a previous report 39 .…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated a pregnancy-specific reduction of unswitched memory-like and transitional-like B-cell subsets 30 , which is in line with a prior study showing that such reduction of B-cells is associated with COVID-19 severity 107 . Thus, given such deficiencies in peripheral adaptive immunity, pregnant women infected with SARS-CoV-2 may rely more heavily on monocytes, which are also potent contributors to anti-viral host defense 108 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In vitro studies detected different cellular immune reactions to SARS-CoV-2 and cytokine secretion in pregnant women compared to non-pregnant women. Especially IL-8 concentration, which has a chemotactic effect on neutrophils and is increased in SARS-CoV-2-positive women [ 25 ].…”
Section: Discussionmentioning
confidence: 99%